Evaluating antimicrobial resistance profiles, UV response, and curli production in Gram-negative river water isolates from the Cape Winelands - Kuster, Margot Ellen (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScFoodSc)--Stellenbosch University, 2024.